2020
DOI: 10.1002/mbo3.1153
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota succession during aerobic stability of maize silage inoculated with Lentilactobacillus buchneri NCIMB 40788 and Lentilactobacillus hilgardii CNCM‐I‐4785

Abstract: Aerobic deterioration of silage following feeding out is responsible for the deterioration of its quality. Inoculation of silage with lactic acid bacteria is one strategy to limit these effects. A trial was performed using whole‐plant corn ensiled in bag silo, and forage was inoculated with Lentilactobacillus buchneri NCIMB 40788 (Lactobacillus buchneri) and Lentilactobacillus hilgardii CNCM‐I‐4785 (Lactobacillus hilgardii) or not (Control silage). After 159 days of fermentation, the silos were opened and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 94 publications
3
30
0
Order By: Relevance
“…Results were consistent with those of previous studies [9,11,12,14,27]. Moreover, Xu et al [26], Drouin et al [28] and Wang et al [29] revealed that Lactobacillus was the dominant bacterial genus in the final whole-plant corn silage. This showed that Lactobacillus usually dominates bacterial community succession in whole-plant corn silage during fermentation.…”
Section: Discussionsupporting
confidence: 91%
“…Results were consistent with those of previous studies [9,11,12,14,27]. Moreover, Xu et al [26], Drouin et al [28] and Wang et al [29] revealed that Lactobacillus was the dominant bacterial genus in the final whole-plant corn silage. This showed that Lactobacillus usually dominates bacterial community succession in whole-plant corn silage during fermentation.…”
Section: Discussionsupporting
confidence: 91%
“…The main LAB species in the silages after ensiling for about 300 d were L. buchneri, L. parafarraginis, L. kefiri, and L. diolivorans (Figure 3b), which belong to L. buchneri group as the sole heterofermentative LAB [25]. However, in previous studies, the main LAB species were L. acetotolerans, L. silagei, L. buchneri, L. odoratitofui, L. farciminis, and L. parafarraginis in whole-plant corn silages (90 d) with low pH (from 3.68 to 3.74) [7], L. plantarum, L. buchneri, and L. brevisi in alfalfa silage (90 d) with high pH (from 4.9 to 5.2) [26], L. plantarum, L. hammesi, L. brevisi, L. coryniformis, and L. piscium in Italian ryegrass silages (42 d) with pH ranging from 4.40 to 5.52 [10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Drouin et al [10] revealed that ensiling whole-plant corn with LAB inoculant improved the aerobic stability of the silage, by maintaining a higher microbial diversity (Shannon index of bacteria and fungi), avoiding the dominance of a few bacteria, and preventing fungi from damaging silage quality. However, in the present study, the fungal communities in S1 and S4 had higher Shannon, Simpson, and Chao1 indexes, and greater aerobic stability, than S2 and S3, but the bacterial communities in S1, S3, and S4 had lower Shannon, Simpson, and Chao1 indexes than S2 (Table 3, Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spore-forming capacity of Bacillus contributes to its survival under ensiling conditions, including a prolonged period in a low pH environment as well as anaerobic conditions. The endospores germinate and the cells grow in the silage when the pH and oxygen concentration are appropriate [ 35 , 36 ]. Queiroz et al [ 37 ] proposed that exposure to air results in a greater amount of Bacillus endospores in the outer layers of silage bales than the central and tightly-packed layers.…”
Section: Discussionmentioning
confidence: 99%